The mechanism of electroacupuncture-mediated improvement in Parkinson’s disease by inhibiting ferroptosis through activating the Nrf2/GPX4 signal pathway - Wang, Min; Zheng, He-Sheng; Ye, Wei-Liang; Mao, Jin-Dong; Zhang, Kun; Yang, Le; Zhao, Ming-Gao; Liu, Shui-Bing; Liu, Rui; Wu, Yu-Mei (Frontiers in Aging Neuroscience, 2025)
IntroductionFerroptosis, an iron-dependent regulated cell death pathway, shares several features of Parkinson’s disease (PD) physiopathology, and efficient neuroprotective therapies are required to prevent DAergic neuron death initiated by ferroptosis. Electroacupuncture (EA), a treasure of Traditional Chinese Medicine, exerted therapeutic effects against PD to avoid the side effects of dopamine (DA)-based therapies. However, its underlying mechanisms still need to be fully understood.MethodsMPTP-induced PD mice were treated with EA to evaluate its neuroprotective effects. Behavioral assessments, histopathological analysis of DAergic neurons, and quantification of ferroptosis biomarkers-including malondialdehyde (MDA), 4-hydroxynonenal (4-HNE), iron, glutathione (GSH), and mitochondrial integrity-were performed. Protein expression levels of SLC7A11, GPX4, ferritin heavy chain 1 (FTH1), and nuclear factor erythroid 2-related factor 2 (Nrf2) were analyzed via immunoblotting. To validate pathway specificity, the Nrf2 inhibitor trigonelline (AT) was co-administered with EA.ResultsEA treatment significantly mitigated MPTP-induced DAergic neuron loss and motor deficits. Mechanistically, EA suppressed ferroptosis by reducing lipid peroxidation and iron accumulation while restoring GSH levels. It upregulated ferroptosis-suppressive proteins SLC7A11, GPX4, FTH1, and Nrf2, alongside ameliorating mitochondrial dysfunction. Crucially, AT administration abolished EA’s protective effects, confirming Nrf2 pathway dependency.DiscussionThese findings demonstrate that EA exerts neuroprotection in PD by inhibiting ferroptosis through activation of the Nrf2/SLC7A11/FTH1/GPX4 signaling axis. This study not only elucidates a novel mechanism underlying EA’s efficacy in PD but also highlights ferroptosis modulation as a therapeutic strategy, bridging traditional medicine with molecular pathophysiology. This study has provided new ideas for exploring the mechanism of EA in PD treatment.